Risk Management Practices and Financial Performance of Small-scale Businesses a Case Study of Mukono Central Division - Derrick Micheal Odongo (Uganda Christian University, 2026)
This study examined how risk management practices affect the financial performance of Small and Medium Enterprises in Mukono Central Division, Uganda. The study focused on three objectives: establishing the effect of risk identification on financial performance, determining the effect of risk assessment on financial performance, and examining the effect of risk monitoring on financial performance. A cross-sectional survey design was used to collect data from 63 SME owners and managers through a structured questionnaire. The data analysis techniques included the use of descriptive statistics, Pearson correlation, and simple regression. The results revealed that risk identification had a strong positive influence on financial performance, with a correlation coefficient of .622 and p < .01, indicating that risk identification explained 38.7% of the variance in financial performance, as revealed by the regression coefficient of β = .622 and p < .01. Though most firms regularly identify financial risk, with a mean of 3.67, very few firms use formal identification techniques, with a mean of 3.05. Risk assessment also revealed a moderately strong positive influence on financial performance, with a correlation coefficient of .587 and p < .01, indicating that risk assessment explained 34.5% of the variance in financial performance, as revealed by the regression coefficient of β = .587 and p < .01.Documenting findings of risk assessments, however, recorded the lowest score of all risk management practices, with a mean of 2.97, indicating that most SMEs do not document the results of their risk assessments. Risk monitoring revealed a moderate positive influence on financial performance, with a correlation coefficient of .541 and p < .01.Evaluating the effectiveness of the risk control measures was the least monitored activity, with the mean at 2.90. In terms of financial performance, the SMEs have the capacity to meet their financial obligations, as indicated by the mean of 3.86. The study established that risk identification, assessment, and monitoring all played important roles in the financial performance of the SMEs, with risk identification having the greatest impact. However, the SMEs undertook the activities in an informal manner without documentation of the results, which lessened their effectiveness. It is recommended that the owners of the SMEs adopt risk management tools, document the results of their risk assessment, monitor their risk control measures, and strive to build financial reserves for unexpected events.
Undergraduate